Civil competency of prospective officers: pre-professional stage of development and system of competencies - Бухун, Андрій Григорович (Pedagogy of Higher and Secondary Education, 2017)
The paper organizes theoretical ideas concerning the development of prospective officers’ civil competence, There has been characterized a preprofessional stage of this development with segregation of the system civil competencies of high school students in unity with knowledge-based, value, activity, procedural and personal components, acquired during military occupation orientation.